rs3918242 variant genotype frequency and increased TIMP-2 and MMP-9 expression are positively correlated with cancer invasion in urinary bladder cancer - Pençe, S.; í–zbek, E.; Ozan Tiryakioğlu, N.; Ersoy Tunali, N.; Pençe, H. H.; Tunali, H. (Cellular and Molecular Biology, 2017)
To study the role of MMP9 and TIMP2 genotypes and expression in predisposition to bladder cancer and relation with metastasis. 100 urinary bladder cancer patients and 100 healthy controls were included in the study. rs3918242 and rs8179090 genotypes were determined with PCR-RFLP. Quantitative real-time polymerase chain reaction was employed to assess the MMP-9 and TIMP-2 expression in tumors and adjacent healthy tissues. Variant genotype (TT) for rs3918242 polymorphism and rs8179090 variant genotype are not associated with bladder cancer risk. rs3918242 genotype was significantly associated with tumor invasion. In contrast with this, rs8179090 genotype has not shown a significant association with tumor invasion. Both SNPs did not show a significant association with metastatic status. MMP-9 was upregulated in tumors in comparison to cancer free tissues. Significant increase in the expression of MMP-9 was also observed in invasive tumors. TIMP-2 expression was significantly increased in tumors in comparison to cancer free tissues and in metastatic tumors in comparison to non-metastatic tumors. Tissues with rs3918242 variant genotype have shown increased MMP-9 expression.  rs3918242 promoter polymorphism of MMP-9 is significantly associated with tumor invasion, however; there is no positive correlation between TIMP-2 rs8179090 promoter polymorphism variant frequency and invasion. MMP-9 and TIMP-2 genes are upregulated in cancerous tissues when compared to normal bladder tissues.